2018
DOI: 10.1002/jso.25057
|View full text |Cite
|
Sign up to set email alerts
|

The value of inflammation based prognostic scores in patients undergoing surgical resection for oesophageal and gastric carcinoma

Abstract: Inflammation based prognostic scores may have a role in patients undergoing resection for oesophageal and gastric cancer. These scores are easily calculable from routinely collected data and could be used as an adjunct to existing staging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 39 publications
1
38
0
3
Order By: Relevance
“…NLR in the blood is a useful indicator to reflect the immune status of the host associated with inflammatory responses. Several studies have reported that high NLR caused by high neutrophil and low lymphocyte count is a significant predictor of poor prognosis in various types of solid cancer, including lung cancer, esophageal cancer, gastric cancer, and colorectal cancer . Our study showed that high NLR at 1 or 6 months postoperatively was a significant predisposing factor for OS.…”
Section: Discussionsupporting
confidence: 56%
“…NLR in the blood is a useful indicator to reflect the immune status of the host associated with inflammatory responses. Several studies have reported that high NLR caused by high neutrophil and low lymphocyte count is a significant predictor of poor prognosis in various types of solid cancer, including lung cancer, esophageal cancer, gastric cancer, and colorectal cancer . Our study showed that high NLR at 1 or 6 months postoperatively was a significant predisposing factor for OS.…”
Section: Discussionsupporting
confidence: 56%
“…The finding that there was a correlation between the Clavien–Dindo grade and both CRP and albumin levels on postoperative day 4 could be interpreted as supporting evidence for this hypothesis. Preoperative albumin concentration is a well known prognostic marker; however, fewer studies have assessed the prognostic value of postoperative albumin. Although a decrease in albumin after surgery probably reflects the systemic inflammatory response to surgery and was associated with higher‐grade complications, decreased albumin levels have been shown to be associated with other adverse outcomes and were independently predictive of survival in multivariable analysis in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…Patients with inoperable disease undergoing ‘open and close’ procedures, with no resection, were excluded. The data set included demographic, treatment and pathology details along with complications. The study was approved by the Queen Elizabeth Hospital clinical audit department.…”
Section: Methodsmentioning
confidence: 99%
“…GPS and prognostic nutrition index (PNI) were constructed as previously described to evaluate inflammatory status prior to chemotherapy and thus determine which score is more reflective of prognosis in patients with gastric cancer [10][11][12].…”
Section: Measurement Of Serum Variablesmentioning
confidence: 99%